L-cysteine transporter-PCR to detect hydrogen sulﬁde-producing Campylobacter fetus - Farace, Pablo Daniel; Morsella, Claudia Graciela; Cravero, Silvio Lorenzo Pedro; Sioya, Bernardo Arturo; Amadio, Ariel; Paolicchi, Fernando; Gioffre, Andrea (2020)
Phenotypic differences between Campylobacter fetus fetus and C. fetus venerealis subspecies allow the differential diagnosis of bovine genital campylobacteriosis. The hydrogensulﬁde production,for example,is atrait exclusive toC.fetus fetus and C. fetus venerealis biovar intermedius. This gas that can be biochemically tested can be produced from L-cysteine (L-Cys). Herein, we report a novel multiplex-PCR to differentiate C. fetus based on the evaluation of a deletion of an ATP-binding cassette-type L-Cys transporter that could be involved in hydrogen sulﬁde production, as previously described. A wet lab approach combined with an in silico whole genome data analysis showed complete agreement between this L-Cys transporter-PCR and the hydrogen sulﬁde production biochemical test. This multiplex-PCR may complement the tests currently employed for the differential diagnosis of C. fetus.